Strategi Rumah Data Kependudukan Terintegrasi dengan “BIONIK SYSTEM” di Kota Bogor - Sujatmiko Baliarto (LITERATUS, 2022)
The purpose of this paper is to discuss and examine the Strategy of the Integrated Population Data House with the "Bionic System". This writing method uses a qualitative descriptive method with strategic analysis techniques using SOAR which functions to identify situations and positions. Data collection techniques through observation and interviews. The result of this paper is a strategy where all Population Data from the Disdukcapil of Bogor City and Socio-Economic Characteristics Data from all Regional Apparatus Organizations (OPD) are integrated, bound through the Population Identification Number (NIK) instrument as the "Primary Key" in one Data House. Bionic System (Big Data and Information based on Population Identification Number / NIK), will process, coordinate, compile and present data from various sources, becoming important information for leaders and Regional Apparatus Organizations (OPD) in Decision Making and Policy Strategies